Post-thoracotomy pain syndrome: seldom severe, often neuropathic, treated unspecific, and insufficient. (4th March 2020) - Arends, Sven; Böhmer, Andreas B.; Poels, Marcel; Schieren, Marc; Koryllos, Aris; Wappler, Frank; Joppich, Robin
Abstract: Background: Post-thoracotomy pain syndrome (PTPS) is reported with a prevalence ranging between 33% and 91% in literature. However, the difference between open (TT) and video-assisted thoracic surgery (VATS) concerning the prevalence and neuropathic character of PTPS has not yet been systematically investigated. Furthermore, knowledge on analgesic treatment and its efficacy is limited. Methods: Structured telephone interviews were conducted with 488 patients 6 to 30 months after TT and VATS. In case of pain, patients received a structured questionnaire including the Leeds Assessment of Neuropathic Symptoms and Signs and Brief Pain Inventory. Results: Prevalence of PTPS was 28.6%. 13.2% of patients had a pain intensity Numeric Rating Scale >3, and 4.6% of patients had a pain intensity Numeric Rating Scale >5. In case of PTPS, 63% of patients suffered from neuropathic pain. Post-thoracotomy pain syndrome was more frequent after TT than after VATS (38.0% vs 29.3%, P < 0.05) and in patients younger than 65 years (42.3% vs 26.4%; P < 0.05). TT resulted more often in neuropathic pain (67.7% vs 43.9%; P < 0.05). Forty six percent of PTPS patients received analgesics: 30.3% nonopioids, 25.2% opioids, 10.9% anticonvulsants, and 1.7% antidepressants. Antineuropathic agents were used in 17.4% of patients with neuropathic pain. In 36.7% of patients, the reported reduction of pain was less than 30.0%. Conclusions: Post-thoracotomy pain syndrome is not as common as estimated. In most cases, pain intensity is moderate, but patients suffering from severe pain require special attention. They are often heavily disabled due to pain. Tissue-protecting surgery like VATS is beneficial for the prevention of PTPS. Analgesic medications are often underdosed, unspecific for neuropathic pain, and insufficient.